Reliability of region of interest calculations in the right atrium on post-mortem CT. (March 2018) - Kelly, Linda; Sutherland, Tom; Dimmock, Matthew; Iles, Linda; O'Donnell, Chris
Highlights: Blood can sediment in cavities following death. Subjective assessment of this sedimentation is not reliable. ROI calculations on PMCT can demonstrate this sedimentation. ROI calculation of post-mortem blood in the right atrium is reliable. Size and location of the ROIs in cavity blood assessment requires strict guidelines.